Hidden dual mathematical symmetry in the genetic code - Nieto-Marín, N.; Nieto-Marín, C. C.; Nieto-Marín, I.; Nieto, J. A. (Frontiers in Applied Mathematics and Statistics, 2024)
We describe the genetic code in terms of numbers that help us to find several dual symmetries. Our formulation can even be rewritten regarding the up-down and right-left dual concepts. We argue that our work may bring many topological tools to studying the DNA molecule, including the Grassmann- Plucker coordinates, which are important in mathematical and physical contexts.